TESTING OF DRUG RELEASE FROM BIOADHESIVE VAGINAL TABLETS - (:unkn) unknown (INFORMA HEALTHCARE, 1992)
To establish an in vitro test method that can predict the drug release and dissolution behaviour of vaginal bioadhesive controlled release tablets, a system was developed and its appropriateness to the in situ conditions was examined. For this purpose, the dissolution rates of vaginal bioadhesive tablets were measured by three different methods. These were, USP dissolution apparatus two and a new vaginal dissolution tester (NVDT) which was developed by us with some modification of the vaginal tablet desentegration apparatus of BP 1988 and, testing in cow vaginas in situ. Four different bioadhesive tablet formulations were used being composed of the drug and the anionic polymer, polyacrylic acid (PAA) and the nonionic polymers, hydroxypropylmethyl cellulose (HPMC) and ethylcellulose (EC). The release profiles of the in vitro and in situ methods were investigated and evaluated kinetically. It was found that NVDT could be used to investigate the drug release from vaginal tablets.
Keywords: ZERO-ORDER RELEASE; MATRIX TABLETS; SYSTEMS; BIOAVAILABILITY; FORMULATION; CELLULOSE